PENGARUH BRAND AMBASSADOR K-POP DAN CITRA MEREK LOKAL TERHADAP KEPUTUSAN PEMBELIAN SKINCARE MEREK WHITELAB DI INDONESIA (The Commercium, 2023)
Marketing communications is an important part of consumer purchasing decisions for a brand. Companies choose brand ambassadors based on the same goal, namely wanting to persuade and invite consumers and the public to buy the products they offer. Founded in March 2020, Whitelab is a skincare company that managed to rank fifth in the best-selling local skincare category in e-commerce. Brand image is a description of the level of consumer confidence and trust in a particular brand. This research aims to find out how K-pop brand ambassadors and local brand image influence the decision to purchase Whitelab brand skincare. This research method uses a quantitative approach. Data was collected using questionnaires and literature study. Questionnaires were used to collect information regarding responses to K-pop brand ambassadors, local brand image, and purchasing decisions. Meanwhile, literature studies are used for theoretical analysis regarding K-pop brand ambassadors, local brand image, and purchasing decisions. The results of the research show that 1. The K-pop brand ambassadors does not partially influence the decision to purchase Whitelab brand skincare. 2. The local brand image partially influences the decision to purchase Whitelab brand skincare. 3. The K-pop brand ambassador and local brand image simultaneously influence purchasing decisions. Whitelab brand skincare.